Fantasy, Dissociation, or Hallucination? Clinical Challenges in the Assessment of Childhood Psychopathology: A Case Report - Fatwa, Ahmad Misbahul Ulum; Merilla, Isna; Yusmadewi, Aaliyah; Imron, Muhammad Istio Hadi Al; Billah, Illa; Suwarti, Ariyani Sri; Algristian, Hafid (Indonesian Scientific Publication, 2025)
Childhood trauma is increasingly recognized as a major contributor to psychopathological outcomes such as hallucinations, dissociative symptoms, and maladaptive fantasy use. This case report explores a 20-year-old female patient with a history of recurrent trauma since early childhood, who developed auditory hallucinations commanding self-harm, dissociative episodes, and persistent escapist fantasy as coping mechanisms. Using a case study approach supported by literature review, we examined the clinical trajectory, psychological symptoms, and coping strategies used by the patient. Findings suggest that early and prolonged trauma may distort reality monitoring and identity integration, with dissociation and fantasy serving as maladaptive emotional regulation tools. This case adds to the understanding of how childhood trauma can produce overlapping features of dissociative and psychotic-like symptoms. The report emphasizes the importance of early screening for dissociation and fantasy-based coping in trauma-exposed adolescents, particularly when hallucinations are present. Early interventions, including trauma-informed psychotherapy and family support, may prevent progression to chronic psychiatric disorders.